Culture-based identification of pigmented Porphyromonas and Prevotella species in primary endodontic infections - Anuradha Rajaram; Vijayalakshmi S. Kotrashetti; Pradeep D. Somannavar; Preeti Ingalagi; Kishore Bhat (Tabriz University of Medical Sciences, 2016)
Background. The most common species isolated from primary endodontic infections are black-pigmented bacteria. These species are implicated in apical abscess formation due to their proteolytic activity and are fastidious in nature. Therefore, the present study was carried out to evaluate the presence and identification of various pigmented Porphyromonas and Prevotella species in the infected root canal through culture-based techniques. Methods. Thirty-one patients with primary endodontic infections were selected. Using sterile paper points, samples were collected from the root canals after access opening and prior to obturation, which were cultured using blood and kanamycin blood agar. Subsequently, biochemical test was used to identify the species and the results were analyzed using percentage comparison analysis, McNemar and chi-squared tests, Wilcoxon match pair test and paired t-test. Results. Out of 31 samples 26 were positive for black-pigmented organisms; the predominantly isolated species were Prevotella followed by Porphyromonas. In Porphyromonas only P. gingivalis was isolated. One of the interesting features was isolation of P. gingivalis through culture, which is otherwise very difficult to isolate through culture. Conclusion. The presence of Prevotella and Porphyromonas species suggests that a significant role is played by these organisms in the pathogenesis of endodontic infections.